2010
DOI: 10.1155/2010/246908
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Resistance of Electroless Ni-Cu-P Ternary Alloy Coatings in Acidic and Neutral Corrosive Mediums

Abstract: Electroless Ni-Cu-P alloy coatings were deposited on the ordinary steel substrate in an acidic hypophosphite-type plating bath. These coatings were characterized by a scanning electron microscope (SEM) and an X-ray diffraction. The micrograph shows that coating presents a nodular aspect and is relatively homogeneous and very smooth. The EDX analysis shows that the coating contains 12 wt.% of phosphorus element with a predominance of nickel element. In addition, the anticorrosion properties of the Ni-Cu-P coati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…So, the protection efficiency is in the range from 12% to 80% without and with different concentration of NiSO 4 . The same results were obtained for the effect of Ni-Cu-P coating on the corrosion of mild steel in different medium (Cisse´et al, 2010;Fang et al, 2015). To confirm the results obtained by potentiodynamic polarization curves and study the inhibition mechanism with more detail, EIS was used.…”
Section: Electrochemical Studysupporting
confidence: 59%
See 1 more Smart Citation
“…So, the protection efficiency is in the range from 12% to 80% without and with different concentration of NiSO 4 . The same results were obtained for the effect of Ni-Cu-P coating on the corrosion of mild steel in different medium (Cisse´et al, 2010;Fang et al, 2015). To confirm the results obtained by potentiodynamic polarization curves and study the inhibition mechanism with more detail, EIS was used.…”
Section: Electrochemical Studysupporting
confidence: 59%
“…It is found that the Ni-Cu-P deposit has the better corrosion resistance than Ni-P and copper deposits (Liu et al, 2015;Liu and Zhao, 2004), or stainless steel in alkaline 50% NaOH (Wang et al, 1992). In other study, it is shown that the mechanism protection of Ni-Cu-P deposit depended on the corrosive medium type (Cisse´et al, 2010).…”
Section: Introductionmentioning
confidence: 85%
“…those that can be deposited individually and those that can be only codeposited. The former group consists of metals that are much nobler than Ni, like Ag [54][55][56][57] and Cu [58][59][60][61][62][63][64][65][66][67][68]; metals that have similar standard potentials, such as Co [69][70][71][72][73][74][75][76] and Sn [77][78][79][80][81][82][83][84][85]; and metals that are more cathodic, like Cr [86,87], Zn [88][89][90][91][92][93][94][95][96][97][98][99][100] and Mn [101]…”
Section: Deposition Of Ni Alloysmentioning
confidence: 99%
“…Ternary Ni-P coatings, such as Ni-Cu-P [2, 3], Ni-W-P [48], Ni-P-PTFE [9, 10], Ni-P-SiC [11, 12], Ni-P-Al 2 O 3 [13, 14], and Ni-P-TiO 2 [1517], have been investigated by different researchers. Among the ternary Ni-P alloy coatings, the electroless Ni-Cu-P alloy presents superior corrosion resistance and thermal conductivity than others [1823]. But, only good corrosion resistant property is not sufficient for industrial purposes.…”
Section: Introductionmentioning
confidence: 99%